Partnerships in Developing Cultural Resources: Lessons From the Task Force on Museums and First Peoples - Nicks, Trudy (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1992)
In 1992 the Task Force on Museums and First Peoples, which was co-sponsored by the Assembly of First Nations and the Canadian Museums Association, published a report which examined outstanding issues between Canadian museums and native peoples and made recommendations for resolving these issues within collaborative partnerships. This paper outlines the background to the Task Force report and discusses its implications for museum anthropology with specific reference to the traditional activities of research, collecting, interpretation and advocacy.